Evolution of a Molluscan Cardioregulatory Neuropeptide - David A. Price (1986)
SYNOPSIS. The cardioexcitatory neuropeptide FMRFamide was first identified from a clam, but has now been demonstrated in several other molluscs. It is probably present throughout the molluscan phylum though co-existing with related peptides in some species. For example, I report here the finding of the peptide phenylalanyl-leucyl-arginyl-phenylalanine amide (FLRFamide) in the mesogastropod Pomacea paludosa where it accounts for 10–20% of the total FMRFamide-like activity. This peptide may be a minor component of the FMRFamide-like activity in other species as well. The pulmonate snails have several, closely-related, heptapeptide analogs of FLRFamide that are unique to them, such as pyroglutamyl-aspartyl-prolyl-phenylalanyl-leucyl-arginyl-phenylalanine amide (pQDPFLRFamide) which was isolated from Helix aspersa. Two additional pulmonate heptapeptides that have been isolated probably differ from pQDPFLRFamide only in their N-terminal amino acid residues. The heptapeptides account for most of the FMRFamidelike activity in the species in which they occur. Though the tetrapeptides FMRFamide and FLRFamide have virtually identical activities on various molluscan tissues, the heptapeptides have activity that is distinct from the tetrapeptides on some pulmonate muscles. 1 have attempted to explain the evolution of this diversity of peptide structure and function found in the modern pulmonates by postulating a gene duplication in the gastropod line leading to them.